Worker Defensive Behavior Associated with Toxins in the Neotropical Termite Neocapritermes braziliensis (Blattaria, Isoptera, Termitidae, Termitinae) - Costa-Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP]; Janei, Vanelize [UNESP]; Esteves, Franciele Grego [UNESP]; dos Santos-Pinto, José Roberto Aparecido [UNESP]; Palma, Mario Sergio [UNESP] (Springer Nature, 2019)
Termite societies are abundant in the tropics, and are therefore exposed to multiple enemies and predators, especially during foraging activity. Soldiers constitute a specialized defensive caste, although workers also participate in this process, and even display suicidal behavior, which is the case with the species Neocapritermes braziliensis. Here we describe the morphology, mechanisms of action, and proteomics of the salivary weapon in workers of this species, which due to the autothysis of the salivary glands causes their body rupture, in turn releasing a defensive secretion, observed during aggressiveness bioassays. Salivary glands are paired, composed of two translucent reservoirs, ducts and a set of multicellular acini. Histological and ultrastructural techniques showed that acini are composed of two types of central cells, and small parietal cells located in the acinar periphery. Type I central cells were abundant and filled with a large amount of secretion, while type II central cells were scarce and presented smaller secretion. Parietal cells were often paired and devoid of secretion. The gel-free proteomic approach (shotgun) followed by mass spectrometry revealed 235 proteins in the defensive secretion, which were classified into functional groups: (i) toxins and defensins, (ii) folding/conformation and post-translational modifications, (iii) salivary gland detoxification, (iv) housekeeping proteins and (v) uncharacterized and hypothetical proteins. We highlight the occurrence of neurotoxins previously identified in arachnid venoms, which are novelties for termite biology, and contribute to the knowledge regarding the defense strategies developed by termite species from the Neotropical region.
Keywords: Autothysis; Chemical defense; Defensins; Proteomics; Saliva; Salivary glands; Self-sacrifice behavior